2007
DOI: 10.1557/jmr.2007.0090
|View full text |Cite
|
Sign up to set email alerts
|

Contact area and size effects in discrete dislocation modeling of wedge indentation

Abstract: Plane strain indentation of a single crystal by a rigid wedge is analyzed using discrete dislocation plasticity. We consider two wedge geometries having different sharpness, as specified by the half-angle of the indenter: α = 70° and 85°. The dislocations are all of edge character and modeled as line singularities in a linear elastic material. The crystal has initial sources and obstacles randomly distributed over three slip systems. The lattice resistance to dislocation motion, dislocation nucleation, disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
(27 reference statements)
2
25
0
Order By: Relevance
“…First, due to material sink-in a portion of the deformed material surface outside the contact tends to become almost parallel to the indenter surface so that when indentation continues and the indenter touches the surface of the crystal, the contact length suddenly increases. Secondly the surface roughens and, as discussed in detail by Widjaja et al [13], this also leads to abrupt increases in contact length. The predicted increase in the contact length a for the circular indenters in figure 3(b) exhibits the same general trend, with occasional jumps in contact length occurring with the average da/dh decreasing for increasing indentation depth.…”
Section: Numerical Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…First, due to material sink-in a portion of the deformed material surface outside the contact tends to become almost parallel to the indenter surface so that when indentation continues and the indenter touches the surface of the crystal, the contact length suddenly increases. Secondly the surface roughens and, as discussed in detail by Widjaja et al [13], this also leads to abrupt increases in contact length. The predicted increase in the contact length a for the circular indenters in figure 3(b) exhibits the same general trend, with occasional jumps in contact length occurring with the average da/dh decreasing for increasing indentation depth.…”
Section: Numerical Resultsmentioning
confidence: 85%
“…• as the contact length is significantly larger [13]. For the larger tip angle, the hardness clearly shows the typical size effect for wedge indentation, levelling off at a constant value of around H = 0.4 GPa at h = 0.4 µm.…”
Section: Hardnessmentioning
confidence: 89%
“…In general, A differs from the nominal contact length A N 2d= tan o due to sink-in or pile-up as sketched in Fig. 1b, but it does not account for surface roughness which, as shown by Widjaja et al (2006), can lead to a significantly smaller contact area in some circumstances and especially for sharp indenters. Perfect sticking is assumed as soon as the wedge comes in contact with the film so the rate boundary conditions applied are…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…In these simulations, ''low source density'' materials were considered with the plasticity size effect mainly resulting from sourcelimited plasticity. Widjaja et al (2005Widjaja et al ( , 2006 reported on two-dimensional simulations for the cylindrical indentation of materials with a wide range of source densities. Over the range of indentation depths considered in these studies, the increasing hardness with increasing indentation depth associated with sharp indenters was not obtained and the cylinder radius played a dominant role.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the experimental observations, computer simulations have greatly contributed to the investigation of the response of materials during nanoindentation. The common modeling methods are finite element [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], crystal plasticity [42][43][44][45][46][47][48][49][50], discrete dislocation dynamics [51][52][53][54][55][56][57][58][59][60][61][62], the quasicontinuum method [63][64][65][66][67][68][69][70][71][72][73]…”
Section: Introductionmentioning
confidence: 99%